CHANGE OF AGROCHEMICAL PROPERTIES OF A FOOTHILL ZONE OF ARMENIA DURING THEIR CULTIVATION (Proceedings of the YSU B: Chemical and Biological Sciences, 2003)
It has been shown that semi-deserted soils of Armenian pre-mountainous zone do not provide high harvest of cultures without irrigation since they lack humus, nitrogen and are rich in carbonic acids. Cultivated both virgin brown semi-deserted and chestnut soils with mixed content of organic compounds, nitrogen, phosphorus and calcium differ from each other a little. Owing to cultivation and irrigation the carbonates move deep from higher horizons to lower ones. Soluble salts of subsoil zone after cultivation and irrigation become mobile. It is natural that a part of salts is washed into deeper horizons with capillary water, and the other part rises to top horizons with capillary waters.
Keywords: semi-deserted soils; pre-mountainous zone; irrigation; capillary water